2020
DOI: 10.3390/molecules25071613
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of 3-Benzylidenechromanones and Their Spiropyrazolines-Based Analogues

Abstract: A series of 3-benzylidenechrmanones 1, 3, 5, 7, 9 and their spiropyrazoline analogues 2, 4, 6, 8, 10 were synthesized. X-ray analysis confirms that compounds 2 and 8 crystallize in a monoclinic system in P21/n space groups with one and three molecules in each asymmetric unit. The crystal lattice of the analyzed compounds is enhanced by hydrogen bonds. The primary aim of the study was to evaluate the anti-proliferative potential of 3-benzylidenechromanones and their spiropyrazoline analogues towards four cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
(39 reference statements)
1
18
0
Order By: Relevance
“…In view of the fact that the resulting 3‐alkylideneflavanones have gathered considerable momentum in the field of medicinal chemistry (Figure 1), [10] this appealing but challenging regiocontrolled strategy would offer a valuable synthetic transformation. Furthermore, in contrast with the conventional methods for the synthesis of 3‐alkylideneflavanones from 2‐hydroxyacetophenones and aromatic aldehydes involving tedious procedures, [10b,c,d] this one‐pot protocol achieved 100% atom‐economy efficiency and displayed excellent functional group tolerance and remarkable regioselectivity under mild reaction conditions.…”
Section: Methodsmentioning
confidence: 98%
“…In view of the fact that the resulting 3‐alkylideneflavanones have gathered considerable momentum in the field of medicinal chemistry (Figure 1), [10] this appealing but challenging regiocontrolled strategy would offer a valuable synthetic transformation. Furthermore, in contrast with the conventional methods for the synthesis of 3‐alkylideneflavanones from 2‐hydroxyacetophenones and aromatic aldehydes involving tedious procedures, [10b,c,d] this one‐pot protocol achieved 100% atom‐economy efficiency and displayed excellent functional group tolerance and remarkable regioselectivity under mild reaction conditions.…”
Section: Methodsmentioning
confidence: 98%
“…Sim et al reported [ 26 ] the use of purinimide-pyrazoline compounds (e.g., derivative 1 ) ( Figure 4 ) and their polyoxometalate complexes as photosensitizers in photodynamic therapy. Recently, Budziz and co-workers documented the biological evaluation of a series of chromanone-spiro-1-pyrazoline hybrids [ 27 ]. Among them, 2 was found to be the most cytotoxic against HL-60, NALM-6, and WM-115 cell lines (IC 50 = 3.0–6.8 μM).…”
Section: 1-pyrazolinesmentioning
confidence: 99%
“…A wide scope of substrates was 18 F‐radiofluorinated within this transformation to generate corresponding 18 F‐labeled products 35 at a moderate RCY. Particularly, 18 F‐labelled compound 35 a was synthesized in 20% RCY (after isolation) from 4‐chromanone, which is a vital scaffold in many anticancer candidates [39] . It is noteworthy that this product (compound 35 a ) was not prepared in their previously reported method and only by‐products were obtained after the reaction was finished.…”
Section: Photo‐aromatic Fluorinationmentioning
confidence: 99%